On a normality criterion of Mandelbrojt - Dovbush, P.V. (Complex variables and elliptic equations, 2014)
Extension of the classical Mandelbrojt's criterion for normality of a family of zero-free holomorphic functions of several complex variables is given. We show that a family of holomorphic functions of several complex variables whose corresponding Levi form is uniformly bounded away from zero is normal.